Membendung Arus Radikalisasi di Indonesia - Arifin, Syamsul (Program Pascasarjana UIN Sunan Ampel Surabaya, 2014)
This paper seeks to examine religious phenomena in the Islamic community in Indonesia which have undergone significant changes since the fall of the New Order regime in 1998. One of the significant changes that drew the attention of some observers is the proliferation of various religious groups that carry radical ideologies. The presence of radical Islamic groups or organizations is never static, but continues to develop in line with the dynamics of the country and global environment. These developments invite public concern and anxiety because the radical Islamic organizations often spread terror, both to civilians and to the perpetrators alike. Is the development of radical Islamic organizations can be dammed? This paper offers education as one of the institutions that can be optimized to promote what is called de-radicalization. The educational institutions mainly run by Muslims are expected to perform these roles in cooperation with other institutions in order to present the face of Islam in Indonesia that is friendly, tolerant, moderate, but still has dignity in the eyes of the world.